2023
DOI: 10.1002/nop2.1608
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between self‐efficacy and physical activity among colorectal cancer patients: A cross‐sectional study

Abstract: Aim To investigate the current status of self‐efficacy and physical activity among Chinese colorectal cancer (CRC) patients and explore the relationship between them. Design A cross‐sectional study. Methods This study was conducted on 282 CRC patients in China. Structured questionnaires were used to collect data on demographic and clinical information, self‐efficacy (Exercise Self‐Efficacy Scale [ESES]) and physical activity (International Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…According to the IPAQ guidelines, 36 International Physical Activity Questionnaire-Short Form scores of < 600, 600–3000 and > 3000 metabolic equivalent of task -min/week were classified as low, moderate, and high PA levels. In consideration of previous research, 37 we classified PA levels into 2 distinct groups: low PA and moderate to high PA.…”
Section: Methodsmentioning
confidence: 99%
“…According to the IPAQ guidelines, 36 International Physical Activity Questionnaire-Short Form scores of < 600, 600–3000 and > 3000 metabolic equivalent of task -min/week were classified as low, moderate, and high PA levels. In consideration of previous research, 37 we classified PA levels into 2 distinct groups: low PA and moderate to high PA.…”
Section: Methodsmentioning
confidence: 99%
“…According to a study on colorectal cancer patients, participation in exercise led to significant improvements in QoL, fatigue, aerobic fitness, sleep, and upper-body strength, and significantly reduced depression, body fat, and fatigue (30). In another study, physical activity in patients with colorectal cancer was found to have a positive and significant association with self-efficacy (31). In a study on lung cancer patients, preoperative exercise training improved cardiorespiratory fitness in patients before pulmonary resection (32).…”
Section: Physical Activity Role In Promotion Of Recovery and Preventi...mentioning
confidence: 99%
“…The response given and effort made when confronted with a problem are affected by self-e cacy [17]. Patients with high self-e cacy will engage in positive health behaviors and have a high level of psychosocial adaptation, quality of life, and selfrespect [18][19][20]. In addition, there is a high correlation between self-e cacy and stoma adaptation [21,22].…”
Section: Introductionmentioning
confidence: 99%